PRAKTIK TRILOGI PENDIDIKAN KI HAJAR DEWANTARA DALAM PEMBENTUKAN KARAKTER MANDIRI DI SMAN 1 KRIAN SIDOARJO - Iskandari, Helen Octania; Jatiningsih, Oksiana (Kajian Moral dan Kewarganegaraan, 2024)
Character education through the Pancasila Student Profile is highly emphasized in the Independent Curriculum, one of which is independent character. However, there are still students whose learning independence is still relatively lacking, such as students who do not have the initiative to learn independently, who still have the habit of copying their friends' work, complaining when given assignments, and so on. Teachers can teach and educate students' character through the Among Method. The Among Method by Ki Hajar Dewantara emphasized that teachers should be able to use this method in the learning process through the motto which became known as the Educational Trilogy "Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, Tut Wuri Handayani". This research aims to describe how teachers interpret the Education Trilogy and their practices in forming independent character in students. This research uses a descriptive qualitative approach with interview and observation data collection techniques. The data source used is a primary data source with data analysis techniques in the form of reduction, presentation and drawing conclusions. The research results show that the teacher at SMAN 1 Krian Sidoarjo interprets the Education Trilogy as a unit that must be carried out by a teacher in interacting with students. In Ing Ngarsa Sung Tuladha, the teacher gives an example in guiding students' learning difficulties and provides examples of good behavior with an independent character. In Ing Madya Mangun Karsa, teachers provide support, enthusiasm and motivation for creativity and create space for discussion or collaboration in groups with students. Meanwhile, in Tut Wuri Handayani, teachers provide encouragement and freedom to develop their potential, make decisions and look for other learning sources.